Pengaruh Konseling terhadap Peningkatan Harga Diri Penderita Kusta - Rozi, Fahrur; Hastuty, Yenni (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Leprosy is an infectious disease that causes very complex problems. The problem that is needed is not only from a medical point of view but also extends to social, economic problems for sufferers, thus allowing a change in the self-esteem of lepers. In this study, researchers used a Pre-trial research design (One-group Pre-test-post test Design). Taking respondents in this study used a consecutive sample technique in which the sample was patients in Sumber Glagah Leprosy Hospital, Pacet District, Mojokerto Regency, which corresponded to the inclusion and exclusion criteria of 30 respondents. The results showed that respondents' self-esteem before counseling was mostly moderate for 26 respondents (86.7%), the self-esteem of respondents after counseling was mostly 20 respondents (66.7%). To analyze the differences in influence on increasing self-esteem, a T test was conducted using SPSS, obtained α = 0,000, where α <0.05, which means H1 was accepted or there was an increase in self-esteem at the Sumber Glagah Pacet Hospital Mojokerto. This involves the counseling factor itself that supports patient knowledge and is an application of the relationship between nurses and patients, so this counseling needs to be supported and programmed to improve patient effectiveness.